Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Solution of integral [tex]\int \frac{ds}{s^{2}(s-1)^{2} }[/tex] is [tex]2ln|\frac{s}{s-1}|-\frac{1}{s}-\frac{1}{s-1}+c[/tex].
We have to evaluate [tex]\int \frac{ds}{s^{2}(s-1)^{2} }[/tex]
By using partial fractions, evaluate the integral
Let [tex]\frac{1}{s^{2}(s-1)^{2} } =\frac{A}{s} +\frac{B}{s^{2}} +\frac{c}{s-1} +\frac{D}{(s-1)^{2} }[/tex]
[tex]1=As(s-1)^{2} +B(s-1)^{2} +Cs^{2}(s-1)+Ds^{2}[/tex]
Put s = 0, 1 = B.1 ⇒ B = 1
Put s= 1, 1 = D ⇒ D = 1
Put s = -1, [tex]1=A(-1)(-2)^{2} +B(-2)^{2} +C(-1)^{2} (-2)+D(-1)^{2}[/tex]
1 = -4A + 4B -2C + D
1 = -4A + 4 -2C + 1
-4 = -4A -2C
2 = 2A + C----------------(1)
Put s = 2, 1 = A(2) + B +C(4) +D(4)
1 = 2A + 1 + 4C +4
-4 = 2A + 4C
-2 = A + 2C---------------(2)
From(1),
C = 2 -2A ---------------(3)
From (2),
⇒ -2 = A + 4 -4A
⇒ -6 = -3A ⇒ A = 2
From (3)
C = 2 - 2(2)
⇒ C = -2
Thus [tex]\int \frac{ds}{s^{2}(s-1)^{2} }= \int (\frac{2}{s} +\frac{1}{s^{2} }- \frac{2}{s-1} +\frac{1}{(s-1)^{2} } )ds[/tex]
= [tex]2 ln|s|-\frac{1}{s} -2ln|s-1|-\frac{1}{s-1}+c[/tex]
= [tex]2ln|\frac{s}{s-1}|-\frac{1}{s}-\frac{1}{s-1}+c[/tex]
Thus,
Solution of integral [tex]\int \frac{ds}{s^{2}(s-1)^{2} }[/tex] is [tex]2ln|\frac{s}{s-1}|-\frac{1}{s}-\frac{1}{s-1}+c[/tex].
Find out more information about integral here
brainly.com/question/18125359
#SPJ4
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.